Possible hazardous components in dental alginates: Physicochemical properties by a mineralogical and spectroscopic investigation - Matteo Ardit; Tommaso Baroni; Fabio Capacci; Giulio Arcangeli; Maurizio Romanelli; Alfonso Zoleo; Silvana Capella; Elena Belluso; Pietro Gabellini; Raffaello Cioni; Francesco Di Benedetto (Elsevier, 2023)
Alginates are products used as impression materials in dentistry and prosthetics. They consist of polymers, calcium alginates mixed with diatomite and additives. Recently, the occurrence of severe silicosis associated with exposure to respirable dust of such materials has increased the scientific interest in understanding how these materials may pose a toxicological problem to workers. The primary objective of this study is to improve the understanding of both the existence and the characteristics of the toxicant(s) contained in these materials, with the goal of better defining the risk assessment for this occupational setting.Two commercial dental alginates were subjected to a mineralogical, microchemical and spectroscopic investigation. The results indicate the presence of a significant amount of diatomite, clearly identified by micromorphology and formed mainly by cristobalite. The respirable fraction of the dust represents at least 30  % of the total number of particles, and this fraction contains a relevant amount of crystalline silica particles. Conversely, the investigated alginate materials do not exhibit the presence of radical species.The results obtained confirm that the cristobalite detected originates from the high-temperature transformation of amorphous silica during the calcination process of diatomite, prior to mixing with the other components. The same process also produces wollastonite (CaSiO3), which, like cristobalite, is a crystalline phase known for its toxicological effects. The present findings call for a rethinking of dental alginates with regard to the definition of their health risks for technical operators.